PENYULUHAN E-COMMERCE SEBAGAI MEDIA PROMOSI PADA UKM (USAHA KECIL MENENGAH) DI MASA PANDEMI COVID 19 - Novi Yona Sidratul Munti (Universitas Pahlawan Tuanku Tambusai, 2021)
The implementation of this community service involves one partner, namely the SME Partner Group located in Rantau Merangin Village. This group has various businesses, including various culinary, clothing, laundry, health and crafts. However, in the current Covid 19 pandemic, there is a lack of promotion and product sales that are still carried out traditionally as well as less professional management or management capabilities, this has caused some SMEs in Rantau Merangin Village to be underdeveloped and even some of them went out of business. The purpose of implementing this community service is to apply e-commerce to the sale of various SME products in Merangin Village with the aim of introducing and increasing sales turnover, while the method used is by using participatory methods, counseling, mentoring and training. The results obtained from the implementation of this community service are that with the assistance of training and e-commerce applications, it can increase the motivation for partners to carry out marketing of their products so that their turnover increases during the Covid 19 Pandemic.